Develop Critical Thinking Skills through Steam Learning in Grade 5 at SD Negeri 2 Sawal Banjarnegara - Lia Fherdiana; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2025)
This study examines the effect of STEAM-based learning on the critical thinking skills of fifth-grade students at SD Negeri 2 Sawal, Banjarnegara. With the need for 21st-century education to develop critical, creative, and innovative thinking in young learners, a quasi-experimental design was used with Pretest-Posttest Nonequivalent Control Groups. Fifth-grade students were divided into experimental and control groups through purposive sampling. A critical thinking test based on Higher Order Thinking Skills (HOTS) was administered before and after the intervention. The results showed a significant improvement in critical thinking skills in the experimental group (p < 0.05). STEAM-based learning effectively enhances critical thinking and is suitable for integration into 21st-century education.